Automatic Feeder Machine with Water Filter System Untuk Budidaya Ikan Nila - Golden R. Modok; Ishak S. Limbong; Verdy A. Koehuan; Murni Pallawagau (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2025)
The fisheries sector is one of the key drivers of the Indonesian economy. One type of fish that is widely cultivated is tilapia. The market demand for tilapia is increasing annually. However, in general, tilapia farmers still employ conventional methods in fish farming, such as feeding fish and maintaining pond cleanliness. Of course, this method is more tiring and requires a lot of time. The purpose of this study is to design an automatic feeder equipped with a filter system to control fish feeding, in conjunction with a water purification system for fish ponds. The study was conducted by building an automatic feeder machine for automatic feeding and an automatic filter to control the quality of water clarity in the pond. From the test results, the amount of feed dispensed by the automatic feeder in 30 seconds, 40 seconds, 50 seconds, and 60 seconds was 142.2 g, 189.9 g, 231.8 g, and 269.2 g, respectively. The throwing distance and distribution of feed were 3 m and 70 °. The proximity sensor is used to control the availability of feed in the storage tube, providing a warning if the amount of feed is less than the minimum limit. The filter system automatically operates when the water turbidity exceeds 40 NTU